Localized smooth muscle differentiation is essential for epithelial bifurcation during branching morphogenesis of the mammalian lung - Kim, Hye Young (Dev Cell, 2015)
The airway epithelium develops into a treelike structure via branching morphogenesis. Here we show a critical role for localized differentiation of airway smooth muscle during epithelial bifurcation in the embryonic mouse lung. We found that during terminal bifurcation, changes in the geometry of nascent buds coincided with patterned smooth muscle differentiation. Evaluating spatiotemporal dynamics of α-smooth muscle actin (αSMA) in reporter mice revealed that αSMA-expressing cells appear at the basal surface of the future epithelial cleft prior to bifurcation, and then increase in density as they wrap around the bifurcating bud. Disrupting this stereotyped pattern of smooth muscle differentiation prevents terminal bifurcation. Our results reveal stereotyped differentiation of airway smooth muscle adjacent to nascent epithelial buds and suggest that localized smooth muscle wrapping at the cleft site is required for terminal bifurcation during airway branching morphogenesis.